What do women want? An analysis of preferences of women, involvement of men, and decision-making in maternal and newborn health care in rural Bangladesh - Ahmed Ehsanur Rahman; Janet Perkins; Shumona Sharmin Salam; Shema Mhajabin; Aniqa Tasnim Hossain; Tapas Mazumder; Shams EL Arifeen (BMC, 2020)
Abstract Background To improve the utilization of maternal and newborn health (MNH) care and to improve the quality of care, the World Health Organization (WHO) has strongly recommended men's involvement in pregnancy, childbirth, and after birth. In this article, we examine women's preferences for men's involvement in MNH care in rural Bangladesh and how this compares to husbands' reported involvement by women. Methods A cross-sectional household survey of 1367 women was administered in 2018 in the district of Brahmanbaria. Outcomes of interest included supporting self-care during pregnancy, participation in birth planning, presence during antenatal care, childbirth, and postnatal care, and participation in newborn care. Binary and multiple logistic regressions were done to understand the associations between the outcomes of interest and background characteristics. Results Although women preferred a high level of involvement of their husbands in MNH care, husbands' reported involvement varied across different categories of involvement. However, women's preferences were closely associated with husbands' reported involvement. Around three-quarters of the women reported having been the primary decision makers or reported that they made the decisions jointly with their husbands. The likelihood of women reporting their husbands were actively involved in MNH care was 2.89 times higher when the women preferred their husbands to be involved in 3-4 aspects of MNH care. The likelihood increased to 3.65 times when the women preferred their husbands to be involved in 5-6 aspects. Similarly, the likelihood of husbands' reported active involvement was 1.43 times higher when they jointly participated in 1-2 categories of decision-making. The likelihood increased to 2.02 times when they jointly participated in all three categories. Conclusion The findings of our study suggest that women in rural Bangladesh do indeed desire to have their husbands involved in their care during pregnancy, birth and following birth. Moreover, their preferences were closely associated with husbands' reported involvement in MNH care; that is to say, when women wanted their husbands to be involved, they were more likely to do so. Programmes and initiatives should acknowledge this, recognizing the many ways in which men are already involved and further allow women's preferences to be realized by creating an enabling environment at home and in health facilities for husbands to participate in MNH care.